Why do projections on China's future food supply and demand differ? - Fan, Shenggen; Agcaoili-Sombilla, Mercedita C. (International Food Policy Research Institute, 1997)
This paper analyzes the macroeconomic assumptions, demand and supply parameters, and structures of the models used in projecting China's future food supply, demand, and trade. Projections from these models vary greatly, from China being almost self-sufficient in grain to becoming a net importer of 369 million metric tons of grain in 2030. The differences arrive mainly in the supply projections (the combined effect of land decline and yield growth). The paper also suggests methodology improvements needed in making future projections of China's grain economy, such as endogenizing government policies, and taking into account the linkage between the agricultural with the non-agricultural sectors, technical change in livestock industry, and infrastructure constraints on grain imports.